An In-Silico Corrosion Model for Biomedical Applications for Coupling With In-Vitro Biocompatibility Tests for Estimation of Long-Term Effects - Šušteršič, Tijana; Simsek, Gorkem Muttalip; Yapici, Guney Guven; Nikolić, Milica; Vulović, Radun; Filipovic, Nenad; Vrana, Nihal Engin (Frontiers in Bioengineering and Biotechnology, 2021)
The release of metal particles and ions due to wear and corrosion is one of the main underlying reasons for the long-term complications of implantable metallic implants. The rather short-term focus of the established in vitro biocompatibility tests cannot take into account such effects. Corrosion behavior of metallic implants mostly investigated in in-vitro body-like environments for long time periods and their coupling with long-term in vitro experiments is not practical. Mathematical modeling and modeling of the corrosion mechanisms of metals and alloys is receiving considerable attention to make predictions in particular for long-term applications by decreasing the required experimental duration. By using such in silico approaches, the corrosion conditions for later stages can be mimicked immediately in in vitro experiments. To this end, we have developed a mathematical model for multi-pit corrosion based on Cellular Automata (CA). The model consists of two sub-models, corrosion initialization and corrosion progression, each driven by a set of rules. The model takes into account several environmental factors (pH, temperature, potential difference, etc.), as well as stochastic components, present in phenomena such as corrosion. The selection of NiTi was based on the risk of Ni release from the implant surface as it leads to immune reactions. We have also performed experiments with Nickel-titanium (NiTi) shape memory alloys. The images both from simulation and experiments can be analyzed using a set of statistical methods, also investigated in this paper (mean corrosion, standard deviation, entropy, etc.). For more widespread implementation, both simulation models, as well as analysis of output images are implemented as a web tool. The described methodology could be applied to any metal provided that the parameters for the model are available. Such a tool can help biomedical researchers to test their new metallic implant systems at different time points with respect to ion release and corrosion and couple the obtained information directly with in vitro tests.